IMPLEMENTASI TEKNOLOGI INFORMASI RESOURCE UPAYA PENINGKATAN LAYANAN DAN MANAJEMEN DATA PERKUBURAN KEPADA MASYARAKAT (Jurnal AbdiMas Nusa Mandiri, 2023)
The Badan Pengelola Perkuburan Islam (BPPI)  is an organization that manages cemeteries and provides burial service facilities to the community. BPPI in managing cemetery data experiences problems in data management and cemetery information service facilities are not updated and are slow. The facts found by the PKM team when visiting BPPI were the lack of data management knowledge and skills in using information technology to manage data and service facilities for the community. These findings prove that BPPI has not implemented information technology in managing cemetery data. Based on these findings, the implementing team has prepared a series of activities using structured training and mentoring methods through Community Based Empowerment (PBM) activities. PBM activities are expected to optimize the application of resource information technology and data management training with information technology as an effort to increase the knowledge and skills of BPPI administrators in managing cemetery data. By implementing hybrid-based resource information technology, administrators are helped in managing cemetery data management and the public can use hybrid-based applications to search and find information on cemetery locations online so that cemetery information services are provided more quickly and accurately. The results that have been achieved from PBM activities are an increase in knowledge by 81.93% and an increase in skills for BPPI administrators by 74.37%.